Reaktionskinetische Untersuchungen der heterogenen Gasphasenoxydation von p-Xylol - P. Felix; G. Gut (CHIMIA)
The kinetic of the heterogeneous gasphase oxidation of p-xylene on a vanadiumoxide catalyst at the temperature range of 315 bo 435 °C has been studied. The experimental data were best fitted by a steady state adsorption model based on the adsorption of oxygen and the reaction of this chemisorbed species with p-xylene in the gasphase. Activation energies for the different reactions are given.